2005
DOI: 10.1021/ac051051n
|View full text |Cite
|
Sign up to set email alerts
|

Using Comprehensive Two-Dimensional Gas Chromatography Retention Indices To Estimate Environmental Partitioning Properties for a Complete Set of Diesel Fuel Hydrocarbons

Abstract: Comprehensive two-dimensional gas chromatography (GCxGC) provides nearly complete composition data for some complex mixtures such as petroleum hydrocarbons. However, the potential wealth of physical property information contained in the corresponding two-dimensional chromatograms is largely untapped. We developed a simple but robust method to estimate GCxGC retention indices for diesel-range hydrocarbons. By exploiting n-alkanes as reference solutes in both dimensions, calculated retention indices were insensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 52 publications
4
121
0
2
Order By: Relevance
“…The second dimension of separation greatly enhances the resolution of the technique, and for complex mixtures such as crude oil and environmental samples the number of components resolved with GC×GC exceeds that resolved with traditional GC by an order of magnitude (Arey et al, 2007;Arey et al, 2005;Bertsch, 2000;Betancourt et al, 2009;Gaines et al, 2006;Liu and Lee, 2000;Phillips and Beens, 1999;Prazen et al, 2001;Wang and Walters, 2007). The instrumentation used for this measurement has been described previously, and details particular to this application are presented as Supplementary Material (Betancourt et al, 2009;Nelson et al, 2006).…”
Section: Gc×gcmentioning
confidence: 99%
“…The second dimension of separation greatly enhances the resolution of the technique, and for complex mixtures such as crude oil and environmental samples the number of components resolved with GC×GC exceeds that resolved with traditional GC by an order of magnitude (Arey et al, 2007;Arey et al, 2005;Bertsch, 2000;Betancourt et al, 2009;Gaines et al, 2006;Liu and Lee, 2000;Phillips and Beens, 1999;Prazen et al, 2001;Wang and Walters, 2007). The instrumentation used for this measurement has been described previously, and details particular to this application are presented as Supplementary Material (Betancourt et al, 2009;Nelson et al, 2006).…”
Section: Gc×gcmentioning
confidence: 99%
“…Several years ago, we developed a simple but robust method to estimate GC × GC retention indices for petroleum hydrocarbons. By exploiting n-alkanes as reference solutes in both dimensions, we were able to calculate retention indices that were insensitive to the uncertainty in the enthalpy of gas-stationary phase transfer for a suite of representative components (Arey et al, 2005). The resulting two-dimensional retention indices can then be used to estimate the liquid vapor pressures, aqueous solubilities, octanol-water partition coefficients, and vaporization enthalpies of a wide range of petroleum hydrocarbons which, in turn, can be used to investigate phase transfer processes affecting petroleum hydrocarbon mixtures in the environment.…”
Section: Results From Prior Supportmentioning
confidence: 99%
“…Evaporation and dissolution act on compounds eluting early on the x-axis and late on the y-axis of GC × GC images, respectively, as described earlier (Arey et al 2005. Evaporation would likely be limited to the time oil resides at the sea surface, as opposed to dissolution, which would occur both in the slick and after deposition into the sediment.…”
Section: Comparison Of Mass Abundances Of ~1400 Individually Tracked mentioning
confidence: 94%
See 1 more Smart Citation
“…Ni et al [26] showed that peak pattern variations over widely varying chromatographic conditions could be modeled well by affine transformations (i.e., translation, scale, and shear). As illustrated in Chapter 3, several approaches have been put forward for two-dimensional indexing [27][28][29][30][31], but none has yet achieved wide acceptance and research continues. A robust approach for dealing with two-dimensional retention-time transformations that can be tailored to specific applications is to locate and identify target peaks relative to the positions of many other peaks in the sample, not just a few standard markers.…”
Section: Chemical Identification By Retention Timementioning
confidence: 99%